2018
DOI: 10.1186/s10194-017-0830-2
|View full text |Cite
|
Sign up to set email alerts
|

The journey from genetic predisposition to medication overuse headache to its acquisition as sequela of chronic migraine

Abstract: Migraine remains one of the biggest clinical case to be solved among the non-communicable diseases, second to low back pain for disability caused as reported by the Global Burden of Disease Study 2016. Despite this, its genetics roots are still unknown. Its evolution in chronic forms hits 2–4% of the population and causes a form so far defined Medication Overuse Headache (MOH), whose pathophysiological basis have not been explained by many dedicated studies. The Global Burden of Disease Study 2016 has not reco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 27 publications
1
22
0
Order By: Relevance
“…However, the quality of the data is limited due to the fact that it is based on post hoc analysis [ 158 ]. A future role for monoclonal antibodies targeting the CGRP pathway is to be awaited [ 159 ]. Ultimately, the identification of proper prophylaxis should be driven by clinical history, comorbidity, contraindications and side effects of the possible drugs [ 126 ].…”
Section: Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the quality of the data is limited due to the fact that it is based on post hoc analysis [ 158 ]. A future role for monoclonal antibodies targeting the CGRP pathway is to be awaited [ 159 ]. Ultimately, the identification of proper prophylaxis should be driven by clinical history, comorbidity, contraindications and side effects of the possible drugs [ 126 ].…”
Section: Treatmentmentioning
confidence: 99%
“…Furthermore, the results from neuroimaging suggest that neuroplasticity exists and that specific imaging findings can be predictive for the outcome after withdrawal. Lastly, the field of genetics in MOH is in development, reaching out to a more personalized approach for MOH [ 159 ].…”
Section: Debates In Mohmentioning
confidence: 99%
“…The employment of multiple treatments, often decided on an empirical basis, could be avoided if the precision medicine approach [ 42 ] was implemented in the management of primary headache. Unfortunately, there have been no specific genetic or epigenetic abnormalities associated with a particular type of headache to assist with determining optimal treatment [ 43 ]. In clinical practice, acute and preventive headache treatments are prescribed on the basis of diagnosis, taking into account the comorbidity of the patient and the safety profile of the drug [ 16 ], but without the possibility of efficient and optimal individualized treatment for the patient.…”
Section: Discussionmentioning
confidence: 99%
“…This finding is consistent with a review that showed high headache frequency to be an important modifiable risk factor in migraine chronification progression [ 44 ] and with previous studies stating that headache frequency in particular may be a risk factor for onset MOH [ 8 , 45 ]. Martelletti shows that MOH must be considered as sequela of chronic migraine and in light of that, it is beneficial to focus on how to reduce headache frequency among migraine patients to avoid MOH as a consequence [ 46 ].…”
Section: Discussionmentioning
confidence: 99%